Agrarianist practices of resolving the agrarian issue during the period of the Ukrainian revolution (1917 – 1921) - Kornovenko, Serhii; Telvak, Viktoria (Ukrainian Peasant, 2021)
Introduction. The authors reveal that one of the phenomena of Central-South-Eastern European history of the second half of the XIX – fi rst third of the XX century, in particular the revolutionary upheavals of the early XX century, was agrarianism. It was the offi cial policy of the governments of Bulgaria, Poland, Romania, Czechoslovakia, and so on. Ukraine in the early twentieth century wasn’t an exception, given the agrarian nature of the then Ukrainian society. During the years of the Ukrainian Revolution of 1917-1921, which, among other things, had a distinctly peasant character, the agrarian practices of P. Skoropadsky and P. Wrangel were marked by the agrarianist content. Purpose. The authors of the article, taking into account the phenomenal nature of agrarianism, the peasant character of the Ukrainian revolution of 1917-1921, aim to study Ukrainian agrarianism (agrarianist practices) as a component of domestic economic governmental policy aimed at solving the agrarian/peasant issue in Ukraine in 1917-1921. Results. First, these leaders understood the peasantry as an active subject of history, the social basis of the state. They also had a corresponding attitude to the peasantry, which is refl ected in legislation and agricultural policy. Second, they understood agricultural policy broadly as a component of domestic economic policy, containing socio-economic and sociopolitical components. Socio-economic part – land reform and settlement of current agricultural affairs: improving land management, improving agro-technical land cultivation, providing peasant households with agricultural equipment, seeds, working cattle and more. Socio-political aspect – forms and methods of cooperation between the authorities and the peasantry, the subjectivization of the peasantry in the current political and legal model of the state. Conclusion. Third, both P. Skoropadsky and P. Wrangel sought not a monarchical, not a socialist, but an alternative way, and were supporters of an innovative model of agricultural development. In their understanding – highly cultured peasant households. Fourth, the instrument of subjectivization of the peasantry – the social basis of the state for them was private peasant ownership of land. The latter was considered the foundation of culture and civilization, the inviolable principle of existence of the state. Providing peasants with private ownership of land and a signifi cant restriction on large land holdings is the cornerstone of the agrarian practices of P. Skoropadsky and P. Wrangel.